2021
DOI: 10.1097/yco.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Towards equitable diagnoses for autism and attention-deficit/hyperactivity disorder across sexes and genders

Abstract: Purpose of reviewSex/gender-related factors contribute to contextual issues influencing the recognition of autism and attention-deficit/hyperactivity disorder (ADHD), and modulate how neurodevelopmental characteristics are manifested. This review summarizes the empirical literature to provide directions for improving clinical diagnostic practices. Recent findingsTiming of autism and/or ADHD diagnosis, particularly in girls/women, is related to the individual's developmental characteristics and co-occurring dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 115 publications
(189 reference statements)
0
26
0
1
Order By: Relevance
“…Previous studies have shown that sex differences are more obvious in individuals with mental development disorders [ 35 ]. Some studies have shown that males diagnosed with ADHD are more likely to accept the diagnosis of oppositional defiance disorder or behavioral disorder, while females are more likely to experience emotional regulation problems [ 36 , 37 ]. However, several studies have shown inconsistent results with our study in regard to how boys are more likely to exhibit symptoms of ADHD [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sex differences are more obvious in individuals with mental development disorders [ 35 ]. Some studies have shown that males diagnosed with ADHD are more likely to accept the diagnosis of oppositional defiance disorder or behavioral disorder, while females are more likely to experience emotional regulation problems [ 36 , 37 ]. However, several studies have shown inconsistent results with our study in regard to how boys are more likely to exhibit symptoms of ADHD [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is represented by the lack of a comparison group constituted by neurotypical individuals which could be relevant in understanding whether the differences emerged can be ascribable to ASD or to child development at a more general level. Despite that, being aware of the females with ASD's interaction profile is crucial when warning signs need to be identified by caregivers and teachers, as well as during the diagnostic process, since many clinicians can be partly influenced by the male bias and other contextual biases ( 8 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons have been suggested for the under-recognition of females, among them: different symptoms manifestation ( 5 ), compensatory and masking behaviors, also referred to as “camouflage” ( 6 , 7 ), and differences in social and communication skills. In particular, females may present better eye contact, facial expressions ( 8 ), better imitative abilities ( 3 , 9 ). Additionally, they might appear more reciprocal ( 10 ) and show relatively preserved pretend play skills ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In children, autistic girls 1 were more likely than boys to over-eat as a means of emotion regulation [23]. Studying sex differences in eating behaviours and psychopathology in autistic children is complicated by the fact that autistic girls are likely to be diagnosed markedly later than autistic boys, especially if they have higher verbal and cognitive abilities [24][25][26][27][28][29]. In adolescence and adulthood, however, there is suggestion that autistic girls and women have more difficulty eating in social contexts than do boys and men [30].…”
Section: Introductionmentioning
confidence: 99%